2021
DOI: 10.1177/2151459321998611
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Extramedullary Versus Intramedullary Reduction in Unstable Femoral Trochanteric Fractures

Abstract: Introduction: The failure rate of operations involving the cephalomedullary nail technique for unstable femoral trochanteric fractures is 3-12%. Changing the reduction strategy may improve the stability. This study aimed to confirm whether reducing the proximal fragment with the medial calcar contact, as opposed to utilizing an intramedullary reduction, would improve the stability of such fractures. Materials and Methods: The unstable femoral trochanteric fracture model was created with fixation by cephalomedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Fukuda et al [ 11 ] stressed the importance of PMCS when they first described the AP3 × ML3 classification. Kawamura et al [ 10 ] confirmed the stability of the extramedullary reduction pattern when mimicking the concept of PMCS in their biomechanical study. Effective bone-on-bone contact is desirable, and the intramedullary type in the lateral view was reported to be a reduction that should be avoided due to the larger sliding distance of the proximal fragments [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Fukuda et al [ 11 ] stressed the importance of PMCS when they first described the AP3 × ML3 classification. Kawamura et al [ 10 ] confirmed the stability of the extramedullary reduction pattern when mimicking the concept of PMCS in their biomechanical study. Effective bone-on-bone contact is desirable, and the intramedullary type in the lateral view was reported to be a reduction that should be avoided due to the larger sliding distance of the proximal fragments [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 82%
“…Recently, the concept of positive medial cortical support (PMCS) has been proposed [ 2 ]. PMCS is defined as slight medial displacement of the cortical bone on the side of the proximal fragment and could provide cortical support between the proximal and distal fragments, thereby resisting further sliding of the proximal fragment [ 9 , 10 ]. A new reduction quality classification for trochanteric fractures, which applies the concept of PMCS, was proposed by Fukuda et al [ 11 , 12 ] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…2). Because anatomic reduction and posterior malreduction have positive contact with the anteromedial cortex [19,40], they were combined. In this study, these three classifications were divided into two groups according to the anteromedial cortex contact (anterior malreduction or other reduction) as the main exposure.…”
Section: Main Exposurementioning
confidence: 99%
“…An observational study among Japanese women suggested that TAD was the most influential factor in cutout [11]. On the other hand, recent studies have reported that anteromedial cortex contact between the neck and diaphyseal fragment affects postoperative instability [6,19,22]. In the past decade, a method for evaluating anteromedial cortex contact using radiographs in the sagittal plane has been reported in East Asia [7,17,19,21,28,38,40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation